The Effectiveness of Mindfulness-Based Therapy on Treatment Adherence and Health Anxiety in Patients with Non-Alcoholic Fatty Liver Disease - Behnavaz, Mitra; Agahheris, Mojgan; Rahmanian, Mahdieh; Kordmirza Nikoozadeh, Ezzatollah (Mental Health and Lifestyle Journal, 2025)
The aim of the present study was to determine the effectiveness of mindfulness-based therapy on treatment adherence and health anxiety in patients with non-alcoholic fatty liver disease. This study was a quasi-experimental design with pretest-posttest and a control group. The statistical population included all patients with non-alcoholic fatty liver disease in Tehran in 2024. From this population, 30 individuals were selected using convenience sampling and randomly assigned to two groups (15 in the experimental group and 15 in the control group). The measurement instruments included the Morisky Medication Adherence Scale (MMAS, 2008) and the Health Anxiety Questionnaire (HAQ-18, 2002). The experimental group underwent mindfulness-based therapy in eight weekly sessions of 90 minutes each, while the control group received no intervention. Data were analyzed using multivariate analysis of covariance (MANCOVA). The results of the analysis indicated that, after controlling for pretest scores, there was a significant difference at the 0.05 level between the experimental and control groups in posttest scores of treatment adherence and health anxiety. It is concluded that mindfulness-based therapy is effective in improving treatment adherence and reducing health anxiety in patients with non-alcoholic fatty liver disease.